Social disadvantage accelerates aging - Kivimaki, Mika; Pentti, Jaana; Frank, Philipp; Liu, Fangyu; Blake, Acer; Nyberg, Solja T.; Vahtera, Jussi; Singh-Manoux, Archana; Wyss-Coray, Tony; Walker, Keenan A.; Partridge, Linda; Lindbohm, Joni V. (Springer Science and Business Media LLC, 2025)
Social disadvantage, like advanced age, is a risk factor for a broad range of health conditions; however, whether it influences the aging process remains unclear. Here, using a multicohort approach, we investigated the associations of social disadvantage with age-related plasma proteins and age-related diseases. We found proteomic signatures of accelerated immune aging and 14 specific age-related proteins linked to social disadvantage during both early and later life. Individuals experiencing social disadvantage had an increased risk of 66 age-related diseases, with up to 39% of these associations mediated by the 14 age-related proteins (for example, DNAJB9, F2, HSPA1A, BGN). The main enriched pathway involved the upregulation of the pro-inflammatory regulator NF-kappa B24 and its downstream factor interleukin-8. Our findings support the hypothesis that social disadvantage throughout the life course may accelerate aging, a biological mechanism that could explain why social stratification plays such a fundamental role in determining human health.